2009
DOI: 10.2353/ajpath.2009.090125
|View full text |Cite
|
Sign up to set email alerts
|

Prion Protein with an Insertional Mutation Accumulates on Axonal and Dendritic Plasmalemma and Is Associated with Distinctive Ultrastructural Changes

Abstract: Prion diseases are fatal neurological diseases characterized by central nervous system deposition of abnormal forms of a membrane glycoprotein designated PrP (prion protein). Tg(PG14) transgenic mice express PrP that harbor a nine-octapeptide insertional mutation homologous to one described in a familial prion disease of humans. Tg(PG14) mice spontaneously develop a fatal neurological illness accompanied by massive apoptosis of cerebellar granule neurons and accumulation of an aggregated and weakly protease-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 38 publications
2
9
0
Order By: Relevance
“…In Creutzfeldt-Jakob disease, the most common prion disease in humans, cerebellar alterations are well documented; 5 notably, flattening and reduction of dendritic arbors of Purkinje cells have been reported 6 . In agreement with the studies above, dendrite degeneration was described as a feature of cerebellar pathology in a mouse model of another human prion disease Gerstmann-Sträussler-Scheinker syndrome 7 . However, synaptic degeneration occurred in the cerebellum infected with a different prion strain (RML) in TG3 mice, a transgenic mouse line in which the prion protein was expressed exclusively in astrocytes 8 .…”
supporting
confidence: 82%
“…In Creutzfeldt-Jakob disease, the most common prion disease in humans, cerebellar alterations are well documented; 5 notably, flattening and reduction of dendritic arbors of Purkinje cells have been reported 6 . In agreement with the studies above, dendrite degeneration was described as a feature of cerebellar pathology in a mouse model of another human prion disease Gerstmann-Sträussler-Scheinker syndrome 7 . However, synaptic degeneration occurred in the cerebellum infected with a different prion strain (RML) in TG3 mice, a transgenic mouse line in which the prion protein was expressed exclusively in astrocytes 8 .…”
supporting
confidence: 82%
“…By colocalization with synaptophysin and synapsin I, fine diffuse small PrP Sc deposits have been shown in presynaptic structures, in the brain of sCJD cases [28]. In contrast, the results of immunogold electron microscopic investigation of Tg( PG14 ) mice that develop a fatal neurological illness accompanied by massive apoptosis of CGN demonstrate that punctate PG14‐PrP accumulates on the plasma membranes of dendrites and axons with no association with pre‐ or post‐synaptic densities and is associated with degenerative changes in dendritic structure [29]. Several studies of infectious prion diseases have shown – in animal models – that PrP Sc accumulates primarily on plasma membranes, at the level of the neuronal cell body and dendrites [30–32] and causes severe synaptic dysfunction before nerve cell death, with dendritic degeneration occurring early in the course of the disease [31,33].…”
Section: Discussionmentioning
confidence: 94%
“… showed mutations of the octapeptide repeat sequence. Tg(PG14) transgenic mice also express a nine‐octapeptide insertional mutation homologous to that of a familial prion disease of humans and these mice transport a weakly protease resistant form of prion protein in axons which accumulates in linear segments on neurite membranes in the region of synaptic terminals . Tg(PG14) mice also show abnormal proliferation of the inner oligodendroglial mesaxon and segmental demyelination although abnormal PrP d has not been specifically detected at these sites .…”
Section: Discussionmentioning
confidence: 99%